Fibroblast Growth Factor-23 and Risk of Cardiovascular Diseases: A Mendelian Randomization Study. Issue 1 (January 2023) - Donovan, Killian; Herrington, William G.; Paré, Guillaume; Pigeyre, Marie; Haynes, Richard; Sardell, Rebecca; Butterworth, Adam S.; Folkersen, Lasse; Gustafsson, Stefan; Wang, Qin; Baigent, Colin; Mälarstig, Anders; et al.
Visual Abstract: Abstract : Background: Fibroblast growth factor-23 (FGF-23) is associated with a range of cardiovascular and noncardiovascular diseases in conventional epidemiological studies, but substantial residual confounding may exist. Mendelian randomization approaches can help control for such confounding. Methods: SCALLOP Consortium data of 19, 195 participants were used to generate an FGF-23 genetic score. Data from 337, 448 UK Biobank participants were used to estimate associations between higher genetically predicted FGF-23 concentration and the odds of any atherosclerotic cardiovascular disease ( n =26, 266 events), nonatherosclerotic cardiovascular disease ( n =12, 652), and noncardiovascular diseases previously linked to FGF-23. Measurements of carotid intima-media thickness and left ventricular mass were available in a subset. Associations with cardiovascular outcomes were also tested in three large case-control consortia: CARDIOGRAMplusC4D (coronary artery disease, n =181, 249 cases), MEGASTROKE (stroke, n =34, 217), and HERMES (heart failure, n =47, 309). Results: We identified 34 independent variants for circulating FGF-23, which formed a validated genetic score. There were no associations between genetically predicted FGF-23 and any of the cardiovascular or noncardiovascular outcomes. In UK Biobank, the odds ratio (OR) for any atherosclerotic cardiovascular disease per 1-SD higher genetically predicted logFGF-23 was 1.03 (95% confidence interval [95% CI], 0.98 to 1.08), and for any nonatherosclerotic cardiovascular disease, it was 1.01 (95% CI, 0.94 to 1.09). The ORs in the case-control consortia were 1.00 (95% CI, 0.97 to 1.03) for coronary artery disease, 1.01 (95% CI, 0.95 to 1.07) for stroke, and 1.00 (95% CI, 0.95 to 1.05) for heart failure. In those with imaging, logFGF-23 was not associated with carotid or cardiac abnormalities. Conclusions: Genetically predicted FGF-23 levels are not associated with atherosclerotic and nonatherosclerotic cardiovascular diseases, suggesting no important causal link. Podcast: This article contains a podcast at https://dts.podtrac.com/redirect.mp3/www.asn-online.org/media/podcast/CJASN/2023_01_10_CJN05080422.mp3